Angler Choices That Help Catch Lots of Big Fish. Issue 5 (28th February 2022) - Bade, Andrew P.; Dippold, David A.; Schmidt, Brian A.; DuFour, Mark R.; Hartman, Travis J.; Ludsin, Stuart A.
Abstract: A primary goal of fisheries management is to maximize angler satisfaction (e.g., by catching more and bigger fish), while maintaining sustainable populations. In addition to environmental and ecological factors, angler choices may influence recreational catches. Using interviews (92, 838) from Walleye Sander vitreus anglers in Lake Erie during 1989–2017, we identified how angler behavior influences catch outcomes. Angler behaviors were associated with changes in catch rate and the length of harvested fish. For example, trolling resulted in a 50% increase in median catch and a 24‐mm increase in length, relative to casting. Other behaviors led to tradeoffs between catch rate and size, such as the time of year anglers fished. We identified behaviors that maximize fishing success with respect to anglers' desired catch outcomes. Our results can help increase angler satisfaction by providing realistic catch expectations, given the environmental and fishery conditions, while improving recreational catch outcomes through more informed angler decision making.